Optimization of culture conditions for biohydrogen production from sago wastewater by enterobacter aerogenes using response surface methodology - Ulhiza, Tami Astie; Mohamad Puad, Noor Illi; Azmi, Azlin Suhaida (Elsevier, 2018)
Sago wastewater (SWW) causes pollution to the environment due to its high organic content. Annually, about 2.5 million tons of SWW is produced in Malaysia. In this study, the potential of SWW as a substrate for biohydrogen production by Enterobacter aerogenes (E. aerogenes) was evaluated. Response Surface Methodology (RSM) was employed to find the optimum conditions. From preliminary optimization, it was found that the most significant factors were yeast extract, temperature, and inoculum size. According to Face Centered Central Composite Design (FCCCD), the maximum hydrogen concentration and yield were 630.67 μmol/L and 7.42 mmol H2/mol glucose, respectively, which is obtained from the sample supplemented with 4.8 g/L yeast extract concentration, 5% inoculum, and incubated at the temperature of 31 °C. Cumulative hydrogen production curve fitted by the modified Gompertz equation suggested that Hmax, Rmax, and λ from this study were 15.10 mL, 2.18 mL/h, and 9.84 h, respectively.